G216 Developing national guidance on specialist and advanced practice for children and young people's nurses. (27th April 2015) - Clarke, D; Hollis, R; Campbell, J; Fairley, I; Flaherty, J; Gelder, C; Houlston, A; Jagger, A; Krinks, K; Smith, F; Tulloh, R
Abstract : Aims: To explore what is meant by advanced practice in CYP nursing. To clarify the distinction between advanced practice, and the roles of nurse specialist, advanced nurse practitioner and nurse consultant. To promote the professional and educational guidance in this 2014 UK document. Methods: A review of the professional literature and a range of national and professional policy documents was undertaken in order to define and establish the competencies and standards for advanced practice in children's nursing, and recognise the value of specialist roles across the UK. A group of expert children's nurses from a range of specialist and generic child health services, worked together to identify the distinction between advanced practice, and the roles of nurse specialist, nurse practitioner, and nurse consultant. Results: The guidance document developed through this project is directed at both commissioners and service providers. It promotes a shared understanding of what is meant by both advanced, and specialist nursing practice, alongside an explanation of the different roles and titles used by nurses and their employers. This is illustrated by the use of real life exemplar nursing roles and services. The document sets out the characteristics of the robust clinical governance framework required to ensure safe and effective care when developing specialist roles and advanced levels of practice. This incorporates accountability and competence frameworks, and educational preparation. Conclusion: The development of innovative nursing roles, working at an advanced level of practice, requires a planned approach to the commissioning and development of services, and of the workforce that is able to deliver them. The guidance document to be discussed in this presentation brings clarity to the concept of advanced practice in child health nursing. It sets out the need for robust, flexible and accessible educational programmes, and the development of comprehensive career frameworks. This presentation will explore the roles of advanced and specialist children and young people's nurses in the UK and promote the professional and educational recommendations of this key document.